Systematic Literature Synthesis of Indonesia’s IT Industry: Ecosystem Capability, Talent Dynamics, and Governance for Digital Competitiveness - Agus Setiawan Agus Setiawan; Siti Nurhayati Siti Nurhayati (Techne: Journal of Engineering, Technology and Industrial Applications, 2025)
This article presents a systematic literature synthesis (SL) of Indonesia’s IT industry with an applied technology orientation, focusing on three interconnected determinants of competitiveness: (i) ecosystem capability and production capacity in software and digital services, (ii) talent pipelines and skills formation under rapid technology change, and (iii) governance and regulation shaping trust, interoperability, and innovation scaling. The SL protocol defines database-specific search strings, eligibility rules, a quality appraisal rubric, and a transparent extraction matrix structured to capture mechanisms rather than merely catalog topics, enabling translation into an operational framework for IT firms, policymakers, and project owners. The synthesis consolidates the evidence into six thematic clusters: industry structure and value-chain positioning, firm-level capability building and maturity, digital transformation demand and procurement patterns, human capital and skills gaps, cybersecurity and trust infrastructure, and policy and institutional enablers. Across themes, the literature converges on a central tension: Indonesia’s IT growth is simultaneously demand-driven and constraint-limited, meaning that expanding digital demand does not automatically translate into sustained competitiveness unless capability formation, talent governance, and standards-based interoperability are engineered as coordinated system components. The article contributes a coherent conceptual framework, copy-ready SL tables for reporting, and figure prompts suitable for Techne submissions, while explicitly distinguishing protocol-based claims from elements that require empirical population through database execution by the authors.